A 5‑year evaluation of chemoprophylactic treatment in elementary school children with subclinical leprosy. Issue 5 (2nd June 2021) - ASTARI‑, LINDA; SARI, NASTITI INTAN PERMATA; NANANG, KUSNARTEDJO; CAHYONO, EDY; HERWANTO, NANNY; LISTIAWAN, MUHAMMAD YULIANTO; ,; ADRIATY, DINAR; ISWAHYUDI, ISWAHYUDI; WAHYUNI, RATNA; ALINDA, MEDHI DENISA; KUSUMAPUTRA, BAGUS HARYO; et al.
No abstract available